Teknologi IoT dan Arduino Guna Pemantauan Arus Dan Tegangan Listrik - Lasarus Setyo Pamungkas; Natalia Damastuti (e-NARODROID, 2018)
ABSTRACT. The technology of electric current and voltage monitoring devices for this decade's strong current is digital kWh meter. As a development of analog kWh meter measuring devices such as those installed in strong current electricity customers PT. PLN Persero. Digital kWh meters calculated function of the power used in kWh and also monitoring of the used current and voltage. The weakness of digital kWh meter results from measurement and monitoring cannot be stored in a long time vulnerable. The aim of this research is design a test device for IOT Flow Monitoring and Strong Current Electric Voltage. A design of test equipment stored in a database with ACS712 current sensor and voltage of ZMPT101B, Arduino microcontroller, ethernet shield, database on localhost and localhost web servers. The design of the current and voltage monitoring test equipment is designed at 1 phase voltage. ACS712 current sensor and ZMPT101B voltage sensor send data to the Arduino microcontroller. The received data is converted to Ampere and Volt values ??and calculated the power and expense ??used by the electricity load. Cost calculation refers to the 1300VA customer cost of PT. PLN Persero about Rp. 1467.28. Then the calculation result data is sent to the database on the localhost server and displayed on the localhost web. The results between digital kWh meters and the design of test equipment obtained an average voltage of 3.8V, 0.71A and 14Watt. Keywords ; Monitoring, Localhost Database ,kWh meter, Current, and power, IoT